Persepsi Guru di Papua terhadap Program Wajib Belajar 12 Tahun - rahmawati, magdalena chori; Edwita, Edwita; Yatimah, Durotul (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
The compulsory education program aims to ensure that every citizen receives a proper basic education. However, the implementation of this program faces various challenges, especially related to the perception of teachers as the main actors in implementing education policies. Based on data from the Central Statistics Agency (BPS) in 2023, Papua Province has the lowest Average Years of Schooling (RLS). This research aims to obtain an overview of the perceptions of teachers in Papua towards the 12 -year compulsory education program and the factors that influence their views. The research method used is a mixed methods sequential explanatory model. The respondents in the research were 20 teachers who taught in various regions in Papua. Data collection was carried out using questionnaires and interviews. The research results show that teachers have a fairly good understanding of the 12 yearcompulsory education program. The teachers recommended several suggestions to increase the effectiveness of the 12-year compulsory education program, such as: building boarding schools, intensive training for teachers, socialization of the program involving community leaders, and a curriculum based on local wisdom.